Nucleobase protection strategy for gene cloning and expression - Kielkowski, Pavel; Brock, Nelson L; Dickschat, Jeroen S; Hocek, Michal (Chembiochem, 2013)
Protecting group chemistry meets molecular biology: Chemically modified dATP carrying a bulky triethylsilylethynyl group was used in a PCR-based synthesis of a gene internally protected against cleavage by restriction endonucleases. The unmodified flanking regions were cleaved for cloning into a plasmid which was replicated by E. coli, and used for protein production.
Keywords: polymerázová řetězová reakce; Polymerase Chain Reaction; klonování DNA; deoxyadeninnukleotidy; Deoxyadenine Nucleotides; plazmidy; exprese genu; Escherichia coli; Gene Expression; Plasmids; Cloning, Molecular